2020
DOI: 10.1111/bcpt.13415
|View full text |Cite
|
Sign up to set email alerts
|

C‐phycocyanin protects against ethanol‐induced gastric ulcers in rats: Role of HMGB1/NLRP3/NF‐κB pathway

Abstract: Gastric ulcer is a widespread inflammatory disease with high socio‐economic burden. C‐phycocyanin is one of the active constituents of Spirulina microalgae, and although it is well known for its antioxidant and anti‐inflammatory properties, its protective effects against gastric ulcer have not yet been identified. High‐mobility group box 1 (HMGB1) is a nuclear protein that, once secreted extracellularly, initiates several inflammatory reactions, and it is involved in the pathogenesis of gastric ulcer. The aim … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 44 publications
3
12
0
Order By: Relevance
“…Phycocyanin has been well documented to exert antiinflammatory effects by inhibiting NF-κB activation in a variety of animal and cellular models of inflammation. [39][40][41] In the present study, PCB showed an equivalent potency to phycocyanin against NF-κB activation and downstream inflammatory responses in human intestine and RAW264.7 cells (Fig. 6, 7b and d), suggesting the critical structural role of PCB in phycocyanin's anti-inflammatory activity.…”
Section: Discussionsupporting
confidence: 58%
“…Phycocyanin has been well documented to exert antiinflammatory effects by inhibiting NF-κB activation in a variety of animal and cellular models of inflammation. [39][40][41] In the present study, PCB showed an equivalent potency to phycocyanin against NF-κB activation and downstream inflammatory responses in human intestine and RAW264.7 cells (Fig. 6, 7b and d), suggesting the critical structural role of PCB in phycocyanin's anti-inflammatory activity.…”
Section: Discussionsupporting
confidence: 58%
“…Hence, oral administration of spirulina-or of spirulina extracts enriched in PhyCB-may have clinical potential for suppressing both the priming and activation of inflammasomes. This proposition is supported by recent cell culture and rodent studies [133,134].…”
Section: Controlling Oxidative Stress With Phycocyanobilinsupporting
confidence: 56%
“…At present, HMGB1 is known to accelerate angiogenesis by 1) acting on vascular endothelium to promoting the formation of new blood vessels and neovascular network by promoting the synthesis of endothelial growth factor. 2) Acetylated HMGB1, which has been released, activates macrophages to upregulate nuclear factor kappa B, thereby promoting the synthesis and secretion of vascular endothelial growth factor and indirectly promoting the formation of new blood vessels ( 38 , 39 ). 3) HMGB1 can upregulate the expression of fibroblast growth factor (FGF) ( 40 ), stimulate the secretion of platelet-derived growth factor (PDGF) ( 41 , 42 ), and greatly enhance the proliferation and migration ability of endothelial cells.…”
Section: Discussionmentioning
confidence: 99%